Challenges, Developments, and Perspectives of Conservation Agriculture (CA) in Modern Agricultural System - Prodipto Bishnu Angon; Shaharia Akter Suchi; Arpita Rani Roy (International Journal of Agronomy)
One of the long-term solutions for agriculture’s depletion of natural resources and degradation of the environment has been identified as conservation agriculture systems with proper crop and soil management. With the progress of the era, great changes have taken place in the field of agriculture. At present, it is possible to produce sufficient crops through conservation agriculture, along with economic, agronomic, and environmental benefits. Conservation techniques greatly lower the danger to food safety on a farm. CA is a farming method used to boost crop yield and sustainability that depends on three principles: minimal soil disturbance, crop rotation, and surface crop residue retention. This paper summarizes the importance, benefits, and challenges of conservation agriculture in a precise manner. In this study, we also discuss the way to increase the practice of conservation agricultureas well as the present research scenario of Bangladesh. At last, some research gaps are highlighted. Through this review, students and researchers will know the current development status of CA clearly and briefly.